2021
DOI: 10.3390/cancers13020262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SOX2, OCT4 and NANOG in Ovarian Cancer Tumor-Initiating Cells

Abstract: The identification of tumor-initiating cells (TICs) has traditionally relied on surface markers including CD133, CD44, CD117, and the aldehyde dehydrogenase (ALDH) enzyme, which have diverse expression across samples. A more reliable indication of TICs may include the expression of embryonic transcription factors that support long-term self-renewal, multipotency, and quiescence. We hypothesize that SOX2, OCT4, and NANOG will be enriched in ovarian TICs and may indicate TICs with high relapse potential. We eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…Previously, we and others found that ALDH1A1 and ALDH1A2 mRNAs were upregulated in TIC growth conditions ( 5 ) and that ALDH activity is increased in TIC-enriching spheroid growth conditions under the influence of RelB transcriptional activity ( 17 ). We selected EOC cell lines with high ALDH activity to test the ALDH1A1 specific inhibitors, NCT-505 and NCT-506.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, we and others found that ALDH1A1 and ALDH1A2 mRNAs were upregulated in TIC growth conditions ( 5 ) and that ALDH activity is increased in TIC-enriching spheroid growth conditions under the influence of RelB transcriptional activity ( 17 ). We selected EOC cell lines with high ALDH activity to test the ALDH1A1 specific inhibitors, NCT-505 and NCT-506.…”
Section: Resultsmentioning
confidence: 94%
“…The TIC population is characterized by enhanced chemoresistance, resistance to cell death, oxidative stress mitigation, and the ability to reestablish cancer after the bulk population is reduced by first line, broad-targeting treatments ( 1 4 ). TIC populations in EOC can be identified by the expression of molecular markers, namely, CD133, NANOG , and SOX2 expression ( 5 ). Despite extensive characterization of identifying markers of TICs, these markers provide little opportunity for therapeutic targeting.…”
Section: Introductionmentioning
confidence: 99%
“…Former investigations pointed out that SOX2 was an interacting protein of PAK2 ( Huttlin et al, 2015 , 2017 ). Besides, SOX2 was reported to be associated with early tumor initiation ( Robinson et al, 2021 ), and its level in high-grade serous carcinoma (HGSC) effusions was demonstrated to be markers of clinically aggressive disease ( Sherman-Samis et al, 2019 ). Additionally, SOX2 expression was found to be positively correlated with the proliferation and migration capacities of tumor cells ( Chen B. et al, 2019 ; Meng et al, 2020 ), and its high expression is a poor prognostic marker for OC.…”
Section: Discussionmentioning
confidence: 99%
“…Following sequential carboplatin treatment of 2D cultured ovarian cancer cell lines, only SOX2 expression remained elevated after the third treatment, suggesting a role for SOX2 in platinum resistance [56]. Knockdown of SOX2 reduced spheroid formation and improved platinum sensitivity [56]. Additionally, while the presence of traditional CSC markers (CD117, CD133, ALDH1) was variable across cell lines, SOX2 was consistently increased in 3D conditions, and elevated in recurrent cases of ovarian cancer, suggesting it may be a more reliable functional marker of CSC and disease recurrence.…”
Section: Stemness Markers Correlate With Therapy Responsementioning
confidence: 98%
“…A recent study by Robinson et al aimed to characterize the roles of SOX2, OCT4, and NANOG in ovarian CSCs [56]. Following sequential carboplatin treatment of 2D cultured ovarian cancer cell lines, only SOX2 expression remained elevated after the third treatment, suggesting a role for SOX2 in platinum resistance [56]. Knockdown of SOX2 reduced spheroid formation and improved platinum sensitivity [56].…”
Section: Stemness Markers Correlate With Therapy Responsementioning
confidence: 99%